Becoming a Champion in Exams: A Case Study of Top Performers in Türkiye’s HEIE - Abdullah Atli; Murat Canpolat; Yeliz Yazıcı Demir (Uluslararası Türk Eğitim Bilimleri Dergisi)
In many countries, securing admission to a prestigious university requires passing various competitive examinations. In Türkiye, the Higher Education Institutions Exam (HEIE) is taken annually by approximately 2-3 million students and is the primary pathway to university admission. Despite an extensive body of literature on exam preparation, research on the characteristics of students who achieve top scores remains limited. Existing studies often lack comprehensive insights into the personal attributes, preparation methods, and overall strategies employed by these high-achieving individuals. This multiple case study aims to fill this gap by examining the experiences of five students who attained top ranks in the HEIE. Through in-depth interviews, we explore four key themes that contribute to their success: personality traits, study strategies, educational background, and sources of support. Our findings offer a nuanced understanding of the factors driving exceptional performance in high-stakes exams, providing valuable implications for educators, policymakers, and students seeking to optimize their preparation for similar competitive assessments.